IbM PRODUK KREATIF IBU-IBU PKK MERUYA SELATAN BERBASIS 3R LIMBAH PADAT PERKOTAAN [IbM: CREATIVITY PRODUCT of PKK SOUTH MERUYA WOMANS BASED ON 3R URBAN SOLID WASTE] - Sawarni Hasibuan; Mirza -; Zulfa Fitri Ikatrinasari (Universitas Pelita Harapan, 2017)
The rapidly increasing quantities of waste generated, especially in urban areas such as Jakarta, becomes a major concern of various stakeholder. With the average of waste per person per day by 1 kg, it is estimated that Jakarta produces 7,000 ton tons of urban waste per day in 2017. The dominant type of urban waste in Jakarta after organic waste is paper waste (18.4%) and plastic waste (13.2%). Present disposal and processing capacity is probably not sufficient to deal with the expected growth. The community's active role in dealing with municipal solid waste issues through the concept of 3R (reduce, reuse, recycle) will reduce the burden of waste that must be transported to the landfill. In South Meruya Village, West Jakarta, two groups of PKK (empowerment of family welfare) women, which are processing urban wastes from plastic solid waste and paper waste. Unfortunately, PKK South Meruya womens have never attended business development training, product quality is also less competitive, not innovative, its market reach is still very limited. The purpose of this activity is to improve the skill of producing quality creative products according to market demand, expand marketing reach by utilizing ICT technology, and improve management of group business. The method used combines lecture approach, mentoring, discussion, simulation and practice. Creative products produced include wallets, bags, ornamental flowers, tissue containers, and cup lamps. Through a partnership with higher education institution, the group of South Meruya PKK women is targeted to increase the quantity and quality of creative products produced, as well as its market reach. Dynamic improvement of understanding and skill of South Meruya PKK mothers in managing urban waste 3R resulted in greenpreneurship model of urban waste-based creative products.